The perception of midwives regarding psychosocial risk assessment during antenatal care - Johanna M. Mathibe-Neke; Allan Rothberg; Gayle Langley (AOSIS, 2014)
Background: The physiological and psychological changes caused by pregnancy may increase a woman's vulnerability to depression, which may in turn have adverse effects on both maternal and foetal wellbeing. Inadequate psychosocial risk assessment of women by midwives may lead to lack of psychosocial support during pregnancy and childbirth. Pregnant women who lack psychosocial support may experience stress, anxiety and depression that could possibly affect foetal wellbeing. Objective:The objective of this study was toexplore and describe the perception of psychosocial risk assessment and psychosocial care by midwives providing antenatal care to pregnant women. Method: An interpretive and descriptive qualitative approach was adopted. Three focus group interviews were conducted with midwives working in three Maternal Obstetric Units in Gauteng Province, using a semi-structured interview guide. The constant comparison data analysis approach was used. Results:Findings revealed that midwives are aware of and have encountered a high prevalence of psychosocial problems in pregnant women. Furthermore, they acknowledged the importance of psychosocial care for pregnant women although they stated that they were not equipped adequately to offer psychosocial assessment and psychosocial care. Conclusion:The findings provided a basis for incorporation of psychosocial care into routine antenatal care.